009A Sample Midterm 3, Problem 4 Detailed Solution

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

Find the derivatives of the following functions. Do not simplify.

(a)  ${\displaystyle f(x)={\frac {(3x-5)(-x^{-2}+4x)}{x^{\frac {4}{5}}}}}$

(b)  ${\displaystyle g(x)={\sqrt {x}}+{\frac {1}{\sqrt {x}}}+{\sqrt {\pi }}}$  for  ${\displaystyle x>0.}$

Background Information:
1. Product Rule
${\displaystyle {\frac {d}{dx}}(f(x)g(x))=f(x)g'(x)+f'(x)g(x)}$
2. Quotient Rule
${\displaystyle {\frac {d}{dx}}{\bigg (}{\frac {f(x)}{g(x)}}{\bigg )}={\frac {g(x)f'(x)-f(x)g'(x)}{(g(x))^{2}}}}$
3. Power Rule
${\displaystyle {\frac {d}{dx}}(x^{n})=nx^{n-1}}$

Solution:

(a)

Step 1:
Using the Quotient Rule, we have
${\displaystyle f'(x)={\frac {x^{\frac {4}{5}}((3x-5)(-x^{-2}+4x))'-(3x-5)(-x^{-2}+4x)(x^{\frac {4}{5}})'}{(x^{\frac {4}{5}})^{2}}}.}$
Step 2:
Now, we use the Product Rule to get

${\displaystyle {\begin{array}{rcl}\displaystyle {f'(x)}&=&\displaystyle {\frac {x^{\frac {4}{5}}((3x-5)(-x^{-2}+4x))'-(3x-5)(-x^{-2}+4x)(x^{\frac {4}{5}})'}{(x^{\frac {4}{5}})^{2}}}\\&&\\&=&\displaystyle {\frac {x^{\frac {4}{5}}[(3x-5)(-x^{-2}+4x)'+(3x-5)'(-x^{-2}+4x)]-(3x-5)(-x^{-2}+4x)({\frac {4}{5}}x^{-{\frac {1}{5}}})}{(x^{\frac {4}{5}})^{2}}}\\&&\\&=&\displaystyle {{\frac {x^{\frac {4}{5}}[(3x-5)(2x^{-3}+4)+(3)(-x^{-2}+4x)]-(3x-5)(-x^{-2}+4x)({\frac {4}{5}}x^{-{\frac {1}{5}}})}{(x^{\frac {4}{5}})^{2}}}.}\end{array}}}$

(b)

Step 1:
First, we have
${\displaystyle g'(x)=({\sqrt {x}})'+{\bigg (}{\frac {1}{\sqrt {x}}}{\bigg )}'+({\sqrt {\pi }})'.}$
Step 2:
Since  ${\displaystyle \pi }$  is a constant,  ${\displaystyle {\sqrt {\pi }}}$  is also a constant.
Hence,
${\displaystyle ({\sqrt {\pi }})'=0.}$
Therefore, we have
${\displaystyle {\begin{array}{rcl}\displaystyle {g'(x)}&=&\displaystyle {({\sqrt {x}})'+{\bigg (}{\frac {1}{\sqrt {x}}}{\bigg )}'+({\sqrt {\pi }})'}\\&&\\&=&\displaystyle {{\frac {1}{2}}x^{-{\frac {1}{2}}}+-{\frac {1}{2}}x^{-{\frac {3}{2}}}+0}\\&&\\&=&\displaystyle {{\frac {1}{2}}x^{-{\frac {1}{2}}}+-{\frac {1}{2}}x^{-{\frac {3}{2}}}.}\end{array}}}$

(a)     ${\displaystyle f'(x)={\frac {x^{\frac {4}{5}}[(3x-5)(2x^{-3}+4)+(3)(-x^{-2}+4x)]-(3x-5)(-x^{-2}+4x)({\frac {4}{5}}x^{-{\frac {1}{5}}})}{(x^{\frac {4}{5}})^{2}}}}$
(b)     ${\displaystyle g'(x)={\frac {1}{2}}x^{-{\frac {1}{2}}}+-{\frac {1}{2}}x^{-{\frac {3}{2}}}}$